Epidemiologic and Molecular Investigation of a MRSA Outbreak Caused by a Contaminated Bathtub for Carbon Dioxide Hydrotherapy and Review of the Literature. (15th April 2020) - Baier, Claas; Ebadi, Ella; Mett, Tobias R.; Stoll, Matthias; Küther, Gerald; Vogt, Peter Maria; Bange, Franz-Christoph
Abstract : Introduction . Methicillin-resistant Staphylococcus aureus (MRSA) is responsible for infections in patients both inside and outside of the hospital and causes outbreaks. Here, we demonstrate the characteristics and control of a MRSA outbreak related to a carbon dioxide hydrotherapy bathtub. Methods . We conducted an outbreak investigation and performed a molecular typing of the outbreak strains with pulsed-field gel electrophoresis (PFGE). In addition, we reviewed PubMed and the Outbreak Database for MRSA outbreaks related to hydrotherapy or other bathing activities. Results . Four patients acquired nosocomial MRSA during the 4-week outbreak period. Environmental sampling revealed the presence of MRSA in the bathtub used for hydrotherapy. The environmental and the patients' isolates showed an indistinguishable restriction pattern in the PFGE. Subsequent discontinuation of bathing stopped the outbreak. The literature search found 9 MRSA outbreak reports related to bathing activities or hydrotherapy. Conclusion . The epidemiologic outbreak investigation together with the molecular findings suggests monoclonal spread of MRSA due to surface contamination of the bathtub. After enhancing the disinfection and cleaning process accompanied by staff training with respect to hand hygiene, no further cases occurred. Standardized and best practice cleaning and disinfection protocols are crucial, especially in critical facilities such as hydrotherapy units. Regular environmental sampling is helpful to monitor these processes and to detect potential contamination.